Juridical Analysis Of Unregistered Kaveling Land Transactions In Batam City - Kelly Kelly; Erniyanti Erniyanti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
Unregistered kaveling land creates legal uncertainty for parties involved in buying and selling transactions. Without a certificate, the legal ownership status of the land remains unclear. Based on the discussions in this thesis, the issues addressed are: 1) Legal Regulations of Unregistered Kaveling Land Transactions. 2) Implementation of Unregistered Kaveling Land Transactions. 3) Constraints and Solutions for Unregistered Kaveling Land Transactions in Batam City. The research method employed is empirical legal research with a qualitative approach. The approaches used include statute approach and conceptual approach. Primary data was obtained through in-depth interviews. The research findings indicate that specific legal regulations governing transactions of unregistered kaveling land are not clearly defined in the law. Nevertheless, land transactions in Indonesia are governed by various regulations, including the Civil Code, Law No. 5 of 1960 on Basic Agrarian Principles, and Government Regulation No. 18 of 2021 concerning Amendments to Government Regulation No. 24 of 1997 on Land Registration. However, there are relevant regulations that also govern aspects related to land transactions in Indonesia. Constraints in the practice of unregistered kaveling land transactions in Batam City include lack of knowledge or understanding among the public regarding land certificate application procedures. The public often perceives sporadic possession letters or Location Determination Maps (PL) as sufficient evidence of legitimate ownership.